Intergenerational earnings mobility and preferences for redistribution - Thomas Siedler; Bettina Sonnenberg (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
This paper analyzes the extent to which intergenerational upward and downward mobility in earnings are related to individuals' preferences for redistribution. A novel survey question from the German Socio-Economic Panel Study - whether the taxes paid by unskilled workers are too high, adequate or too low - are used to elicit attitudes toward redistribution. Intergenerational mobility with regard to long-term earnings is measured using a rich panel data spanning an observation window of 22 years. The results reveal that intergenerational mobility is significantly related to preferences for redistribution. The empirical results yield strong and robust support for Piketty's (1995) rational-learning theory: individuals who experience upward (downward) intergenerational mobility are less (more) likely to favor redistribution taxation policies.
Keywords: J62; H23; 330; labour; family and networks; subjective indicators